Tribenzylbis(triphenylarsine oxide-kappa O)tin(IV) tetraphenylborate - Keng, T.C.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The crystal structure of the title salt, [Sn(C7H7)(3)(C18H15AsO)(2)][B(C6H5)(4)], consists of discrete cations and anions; the tin atom of the cation is five-coordinated in a distorted trans-C3SnO2 trigonal-bipyramidal geometry [summation of C-Sn-C angles 360.0 (3)degrees and O-Sn-O angle 173.1 (1)degrees]. The structure contains voids of 113 (19) angstrom(3), but no solvent molecule could reasonably be located there.